A 'Marginal' tale: the development of the neocortical layer 1. (February 2021) - Gesuita, Lorenzo; Karayannis, Theofanis
Highlights: Developing neocortical layer 1 is a dynamic scene of multiple transient phenomena. The Glutamatergic Cajal–Retzius cells tile the developing cortex, but disappear early postnatally. GABAergic interneurons take over layer 1 as Cajal–Retzius cells disappear. Adult layer 1 has at least four GABAergic inhibitory cell types and is full of local and distal axon-dendritic processes. Layer 1 plays a crucial role in integrating bottom-up and top-down signals. Abstract : The development of neocortical layer 1 is a very dynamic process and the scene of multiple transient events, with Cajal–Retzius cell death being one of the most characteristic ones. Layer 1 is also the route of migration for a substantial number of GABAergic interneurons during embryogenesis and where some of which will ultimately remain in the adult. The two cell types, together with a diverse set of incoming axons and dendrites, create an early circuit that will dramatically change in structure and function in the adult cortex to give prominence to inhibition. Through the engagement of a diverse set of GABAergic inhibitory cells by bottom-up and top-down inputs, adult layer 1 becomes a powerful computational platform for the neocortex.